A comparative study on flank wear and work surface finish during high speed milling of cast iron with different carbide tools - Khan, Ahsan Ali; Aman Nor Rasid, Zuraida; Yusof, Izausmawati (International Islamic University Malaysia, 2011)
Abstract. Tool life sharply reduced for all the carbide tools while increasing cutting speed twice (from 500m/min to 1000m/min) during machining cast iron. Though the productivity would be double at the speed of 1000m/min than that at the speed of 500m/min, tool wear increases to a few times which indicates that the inserts used are not suitable for machining at a high speed like 1000m/min. It is better to cut cast iron using uncoated K20 carbide at low cutting speed rather than at high speed. TiAlN coated carbide has the best wear resistance at both speeds.